2006
DOI: 10.1158/0008-5472.can-05-2728
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Human LAG-3 Molecule Amplifies theIn vitroGeneration of Type 1 Tumor-Specific Immunity

Abstract: The adjuvant activities of the human lymphocyte activation gene-3 (LAG-3) molecule have been evaluated in a human setting by investigating the ability of a soluble recombinant human LAG-3 protein (hLAG-3Ig) to enhance the in vitro induction of viral-and tumor-specific CTLs. We found that soluble human LAG-3 significantly sustained the generation and expansion of influenza matrix protein Melan-A/MART-1 and survivin-specific CD8 + T lymphocytes in peripheral blood mononuclear cells (PBMC) of both cancer patients… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 47 publications
1
52
0
Order By: Relevance
“…As a soluble fusion protein, LAG-3 has also been shown to bind MHC II with a much higher avidity than CD4 (27), to increase the capacity of MHC II-positive macrophages and immature dendritic cells to induce T cell responses in vitro (28), and to enhance the in vitro induction of viral and tumor-specific cytotoxic T cells (29). Accordingly, the LAG-3 fusion protein has been suggested as a potential adjuvant for cancer vaccines (29), including those for melanoma, for which most attempts at immunotherapy have met with little clinical success.…”
mentioning
confidence: 99%
“…As a soluble fusion protein, LAG-3 has also been shown to bind MHC II with a much higher avidity than CD4 (27), to increase the capacity of MHC II-positive macrophages and immature dendritic cells to induce T cell responses in vitro (28), and to enhance the in vitro induction of viral and tumor-specific cytotoxic T cells (29). Accordingly, the LAG-3 fusion protein has been suggested as a potential adjuvant for cancer vaccines (29), including those for melanoma, for which most attempts at immunotherapy have met with little clinical success.…”
mentioning
confidence: 99%
“…A sequences of the T-cell responses to HBsAg. It is possible to explain approximately 5-10% of healthy vaccine recipients fail to produce protective levels of antibodies to the hepatitis B vaccine after standard immunization [28][29][30][31][32] . Although confirming the conclusion is challenging, there are 3 possible factors link to the phenomenon: the happen of the events by chance (because only 15 patients with PRSS1 gene mutation were researched), the patient's human leukocyte antigen genetype and the incongruent immune response to the vaccine components [33] .…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, APC of PBMC exposed in vitro to peptide and hLAG-3Ig displayed a more mature phenotype than APC of PBMC exposed to peptide only, suggesting that the hLAG-3Ig adjuvant effect could have been dependent on activation of circulating APC (14). To evaluate whether hLAG-3Ig worked by a direct mechanism in the induction of DC maturation, iMoDC (100% CD11c ϩ and CD1a ϩ , data not shown) were matured with hLAG-3Ig and assessed for their phenotype.…”
Section: Soluble Hlag-3ig Recombinant Protein Induces Phenotypic Matumentioning
confidence: 91%
“…Several data have been reported on the ability of human rLAG-3 protein (hLAG-3Ig) to work as an adjuvant in in vivo mouse model (12, 13) and we and others have recently showed that soluble rhLAG-3Ig is able to enhance the in vitro induction of viral-and tumor-specific CTL in humans (14,15).…”
mentioning
confidence: 99%